Implementasi dan Evaluasi Visualisasi Data Interaktif pada Publikasi Laporan Bulanan Data Sosial Ekonomi Indonesia - Hafidz Isa Nasruddin Lizana; Farid Ridho (Politeknik Statistika STIS, 2021)
Every month BPS publishes the book LBDSE Indonesia, in which the publication contains the development of 18 data topics and their visualizations. However, the data visualization in LBDSE publications is incomplete and only static, while the existing data has quite large dimensions/variables. So that researchers think to implement interactive data visualization of LBDSE publications on SIVIS LBDSE in order to make it easier to understand the data. To assess the success of the implementation objectives, researchers will evaluate the data visualization on SIVIS LBDSE based on user ratings using 8 assessment indicators adopted from previous research. The purpose of this study is to implement interactive data visualization on LBDSE data, evaluate data visualization on SIVIS LBDSE, and find out the best data visualization for LBDSE publication categorical data. With the help of 50 respondents, they assessed that the data visualization in SIVIS LBDSE has its advantages and disadvantages, each based on the 8 assessment indicators used. But overall the respondents ranked the best data visualization for categorical data in a row, namely, Bar Chart, Tree Map, Bubble Map, and Pie Chart.